2008
DOI: 10.1016/j.yjmcc.2008.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of A2B adenosine receptor in A2A adenosine receptor knockout mouse coronary artery

Abstract: In this study, we looked into possible compensatory changes of other adenosine receptors (AR) in A 2A genetic knockout mice (A2AKO) as well as the functional role of nitric oxide (NO) in A 2A ARmediated vasodilation. Gene expression of ARs from coronary arteries of A 2A AR wild type mice (A2AWT) and A2AKO were studied using real time-PCR. Functional studies were carried out in isolated heart and isolated coronary artery preparations. A 2B AR was found to be 4.5 fold higher in A2AKO than in A2AWT, while A 2A AR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
63
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 59 publications
(74 citation statements)
references
References 38 publications
(69 reference statements)
11
63
0
Order By: Relevance
“…With difficulties in collecting large amount of tissues for Western blot, one of our recent studies has confirmed the absence of A 2A AR protein level in A 2A AR KO mice in isolated coronary arteries using immunohistochemistry [40]. Our functional data also confirmed the lack of CGS-21680 (a selective A 2A AR agonist)-induced coronary flow response in isolated hearts of A 2A AR KO mice and the lack of BAY 60-6583 (a selective A 2B AR agonist)-induced coronary flow response in isolated hearts of A 2B AR KO mice [16,20].…”
Section: Animalssupporting
confidence: 82%
See 4 more Smart Citations
“…With difficulties in collecting large amount of tissues for Western blot, one of our recent studies has confirmed the absence of A 2A AR protein level in A 2A AR KO mice in isolated coronary arteries using immunohistochemistry [40]. Our functional data also confirmed the lack of CGS-21680 (a selective A 2A AR agonist)-induced coronary flow response in isolated hearts of A 2A AR KO mice and the lack of BAY 60-6583 (a selective A 2B AR agonist)-induced coronary flow response in isolated hearts of A 2B AR KO mice [16,20].…”
Section: Animalssupporting
confidence: 82%
“…Mice were kept in cages with 12:12-h light-dark cycles and maintained on a standard laboratory diet with access to water ad libitum. The absence of A 2A and A 2B ARs at mRNA level in A 2A AR KO and A 2B AR KO mice has been confirmed by our previous studies using PCR in isolated aortas, mesenteric arteries, and coronary arteries [16,20,[39][40][41]. With difficulties in collecting large amount of tissues for Western blot, one of our recent studies has confirmed the absence of A 2A AR protein level in A 2A AR KO mice in isolated coronary arteries using immunohistochemistry [40].…”
Section: Animalssupporting
confidence: 55%
See 3 more Smart Citations